CO-tolerant electrocatalysts for hydrogen fuel cells: Fundamental study-based design and real-life applications - Byeon, Jaeho; Kim, Seongbeen; Lee, Seonggyu; Jang, Jong Hyun; Kim, Soo-Kil; Lee, Jinwoo (Elsevier BV, 2024)
Fuel cells are widely used for converting the energy released by fuel oxidation into electricity. Among the available fuels, hydrogen is particularly crucial for achieving carbon neutrality and is mainly produced by natural gas reforming, therefore containing ppm-level traces of carbon monoxide (CO). Despite its low concentration, CO interferes with the operation of hydrogen fuel cells by strongly binding to the anode catalyst and thus irreversibly decreasing its activity (poisoning). To address this problem, which cannot be solved without a deep understanding of all aspects, the present review examines the origins of CO poisoning and categorizes and discusses the related prevention methods, revealing the pivotal role of electrocatalyst design in poisoning research and mitigation. The presented evidence demonstrates that knowledge-driven approaches enable the practical applications of catalysts designed using the above methods and therefore help solve the problems posed by CO poisoning in fuel cells.